2006
DOI: 10.1364/ol.31.000017
|View full text |Cite
|
Sign up to set email alerts
|

High-power single-polarization and single-transverse-mode fiber laser with an all-fiber cavity and fiber-grating stabilized spectrum

Abstract: Conventionally, large-mode-area (LMA) fiber lasers use free-space polarizing components to achieve linear polarization output. External components, however, significantly limit laser robustness and power scalability. We demonstrate, to the best of our knowledge, the first high-power all-fiber cavity single-polarization single-transverse-mode LMA fiber laser, without the use of free-space polarizing components. This has been achieved by using tightly coiled high-birefringence 20 microm core LMA fiber. The lasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Currently, the fiber Bragg grating (FBG) is the key component for the high power clad-pumped all-fiber laser. The FBG can be written into the matched passive fiber by the ultraviolet 248 nm excimer laser, and then is spliced into the rare-earth doped fiber to realize the all-fiber laser, such as: the 405 W single-mode Yb 3+ -doped fiber laser [5], 43 W narrow linewidth Er 3+ :Yb 3+ -doped fiber laser [6], and 39 W few-mode Tm 3+ -doped fiber laser [7]. The FBG was also directly written into rare-earth ions doped fiber core using fs laser sources [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the fiber Bragg grating (FBG) is the key component for the high power clad-pumped all-fiber laser. The FBG can be written into the matched passive fiber by the ultraviolet 248 nm excimer laser, and then is spliced into the rare-earth doped fiber to realize the all-fiber laser, such as: the 405 W single-mode Yb 3+ -doped fiber laser [5], 43 W narrow linewidth Er 3+ :Yb 3+ -doped fiber laser [6], and 39 W few-mode Tm 3+ -doped fiber laser [7]. The FBG was also directly written into rare-earth ions doped fiber core using fs laser sources [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Kurkov et al reported a singlepolarization Er-doped fiber laser using a long-period fiber grating as an intracavity polarizer and obtained a polarization purity of 98% [3]. Chi-Hung Liu et al reported a high power single-polarization fiber laser based on bulk-optical configuration that operated under continuous-wave (CW) regime [4]. The second type of method is making polarization state selection by coinciding reflectivity peaks of different cavity mirrors.…”
Section: Introductionmentioning
confidence: 99%
“…Monolithic fiber lasers present several advantages over systems based on free space elements: they are more compact, alignment-free, and most importantly stable laser emission is therefore easier to achieve. To date, several LMA SIF-based high power laser systems presenting monolithic architectures have been demonstrated [5], [6]. However, LMA PCF-based laser and amplifier systems typically employ several free space sections, occupying large footprints and requiring complex and sensitive alignment Manuscript procedures which strongly influence the laser output stability, performances and handling [7]- [9].…”
Section: Introductionmentioning
confidence: 99%